Penile Replantation: A Retrospective Analysis of Outcomes and Complications - Morrison, Shane D.; Shakir, Afaaf; Vyas, Krishna S.; Remington, Austin C.; Mogni, Benjamin; Wilson, Stelios C.; Grant, David W.; Cho, Daniel Y.; Rahnemai-Azar, Amir A.; Lee, Gordon K.; Friedrich, Jeffrey B.; Mardini, Samir (Journal of Reconstructive Microsurgery, 2017)
Purpose Penile replantation is an uncommonly performed procedure, which can alleviate physical and psychosocial sequelae of penile amputation. This study critically appraises the current literature on penile replantation.Methods A comprehensive literature search of the Medline, PubMed, and Google Scholar databases was conducted with multiple search terms related to penile replantation. Data on outcomes, complications, and patient satisfaction were collected.Results A total of 74 articles met inclusion criteria. One hundred and six patients underwent penile replantation, but outcome, complication, and satisfaction data were not standardized across all patients. Penile amputation most often resulted from self-mutilation or trauma. The majority were complete amputations (74.8%). Full sensation was maintained in 68.4% of patients. Most reported adequate urinary function (97.4%) and normal erection (77.5%). Skin necrosis (54.8%) and venous congestion (20.2%) were the most common complications. Urethral stricture (11.0%) and fistula (6.6%) were common urethral complications. Most (91.6%) patients reported overall satisfaction although there was a lack of patient-reported outcomes. Multivariate analysis suggested that complete amputation (β = 3.15, 95% CI 0.41–5.89, p = 0.024), anastomosis of the superficial dorsal artery (β = 9.88, 95% CI 0.74–19.02, p = 0.034), and increasing number of nerves coapted (β = 1.75, 95% CI 0.11–3.38, p = 0.036) were associated with favorable sexual, urinary, and sensation outcomes. Increasing number of vessels anastomosed (β = −3.74, 95% CI −7.15 to −0.32, p = 0.032) was associated with unfavorable outcomes.Conclusion Although penile replantation is associated with complications, it has a high rate of satisfaction and efficacy. Coaptation of multiple nerves and anastomosis of the superficial dorsal artery should be completed.
Keywords: penis; penile replantation; microsurgery; outcomes; quality of life